Nocturnal dipping is preserved in children with sleep disordered breathing regardless of its severity1. Issue 11 (29th June 2013) - Horne, Rosemary S.C.; Yang, Joel S.C.; Walter, Lisa M.; Richardson, Heidi L.; O'Driscoll, Denise M.; Foster, Alison M.; Wong, Shi; Ng, Michelle L.; Bashir, Farhat; Patterson, Ruth; Jolley, Damien; Walker, Adrian M.; et al.
Abstract Objective Sleep disordered breathing (SDB) in adults has been associated with a loss of nocturnal dipping in blood pressure (BP) and heart rate, however, there have been limited studies in children. We measured BP non‐invasively and continuously overnight in 105 children aged 7–12 with a range of severities of SDB and 36 non‐snoring controls to examine nocturnal dipping profiles. Study Design Children with SDB were divided into three severity groups according to their obstructive apnea hypopnea index. Nocturnal dipping profiles across sleep stages were described both as a proportion of children exhibiting a ≥10% fall in systolic arterial pressure (SAP) and heart rate (HR) from wake to sleep and according to SAP sleep/SAP wake ratio as extreme dippers (ratio ≤ 0.8), dippers (ratio < 0.8 and ≤0.9), non‐dippers (ratio < 0.9 and ≤1.0), and reverse dippers (ratio > 1.0). Results The mean fall in BP between wake and NREM 1/2, SWS, and REM sleep was not different between the groups and there were no differences between the dipping profiles of children in each group. Conclusions SDB did not alter nocturnal dipping patterns of BP and HR compared to controls, a finding which may suggest that these young children have not been exposed to the effects of SDB long enough or that SDB severity was not great enough to affect nocturnal dipping profiles. However, further studies are required to determine if the elevated BP previously reported in this group of children will have long‐term effects on the cardiovascular system. Pediatr Pulmonol. 2013; 48:1127–1134. © 2013 Wiley Periodicals, Inc.